Local and Systemic Immunity Are Impaired in End-Stage-Renal-Disease Patients Treated With Hemodialysis, Peritoneal Dialysis and Kidney Transplant Recipients Immunized With BNT162b2 Pfizer-BioNTech SARS-CoV-2 Vaccine - Piotrowska, Magdalena; Zieliński, Maciej; Tylicki, Leszek; Biedunkiewicz, Bogdan; Kubanek, Alicja; Ślizień, Zuzanna; Polewska, Karolina; Tylicki, Piotr; Muchlado, Marta; Sakowska, Justyna; Renke, Marcin; Sudoł, Adam; et al. (Frontiers in Immunology, 2022)
Vaccination against COVID-19 in patients with end-stage renal disease (ESRD) on replacement therapy and kidney transplant recipients (KTRs) is particularly important due to the high mortality rate. Here, we tested the local and systemic immunity to the novel Pfizer BioNTech (BNT162b2) messenger RNA (mRNA) in ESRD, KTR patients, and healthy individuals (150 subjects). The ESRD group was divided into: hemodialysis (HD) and peritoneal dialysis (PD). We investigated the local and systemic immunity based on anti-N (nucleoprotein) and anti-S (spike1/2) Immunoglobulin A (IgA) and Immunoglobulin G (IgG) antibodies, respectively. Additionally, we performed an Interferon gamma (IFN-γ) release test Interferon-gamma release assay (IGRA) to monitor the cellular component of vaccine response. The control group had the highest level of anti-S IgG antibodies (153/2,080 binding antibody units (BAU)/ml) among all analyzed patients after the 1st and 2nd dose, respectively. The HD group (48/926 BAU/ml) had a diminished antibody level compared to PD (93/1,607 BAU/ml). Moreover, the seroconversion rate after the 1st dose was lower in HD than PD (56% vs. 86%). KTRs had extremely low seroconversion (33%). IgA-mediated immunity was the most effective in the control group, while other patients had diminished IgA production. We observed a lower percentage of vaccine responders based on the IFN-γ level in all research participants (100% vs. 85% in control, 100% vs. 80% in PD, 97% vs. 64% in HD). 63% of seropositive KTRs had a positive IGRA, while 28% of seronegative patients produced IFN-γ. Collectively, PD patients had the strongest response among ESRD patients. Two doses of the Pfizer vaccine are ineffective, especially in HD and KTRs. A closer investigation of ESRD and KTRs is required to set the COVID-19 vaccine clinical guidance. Clinical Trial Registration Number www.ClinicalTrials.gov, identifier: NCT04 905 862